Becoming the Idol: Quantitative Content Analysis of KPopfication in Clash of Champion Casts - Pramesthi, Jasmine Alya (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
This study employs a quantitative content analysis method to explore the phenomenon of KPopification in the context of Clash of Champion casts, a student competition organized by Ruang Guru. Although the casts are not K-Pop idols, an analysis of 300 tweets reveals that social media audiences often apply K-Pop culture's terms and norms to them. By analyzing the frequency of keywords such as